LC–MS/MS determination of ginsenoside compound K and its metabolite 20 (S)-protopanaxadiol in human plasma and urine: applications in a clinical study. (15th March 2019) - Yang, Li; Wang, Chun-Yang; Xie, Xiao-Nv; Wang, Yi-Cheng; Peng, Jing-Bo; Huang, Wei-Hua; Chen, Yao; Ouyang, Dong-Sheng; Tan, Zhi-Rong
Aim: Ginsenoside compound K (CK) is considered to be a potential therapeutic drug for rheumatoid arthritis because of its good anti-inflammatory activity. The purpose of this work was to establish a rapid, sensitive and specific method for determination of CK and its active metabolite 20( S )-protopanaxadiol (20( S )-PPD). Materials & methods: The analytes and internal standards were extracted by liquid–liquid extraction. Then, were separated by high performance liquid phase and determined by triple quadrupole mass spectrometry.Results: A LC–MS/MS using liquid–liquid extraction was developed for determining CK over the concentration range 1.00–1002.00 ng/ml and 0.15–54.30 ng/ml for 20( S )-PPD. The lower limits of quantification for CK and 20( S )-PPD were 1.00 and 0.15 ng/ml, respectively.Conclusion: This method was successfully validated for detecting both CK and 20( S )-PPD in the human plasma and urine, and was proved to be suitable for the pharmacokinetic study of CK in healthy Chinese volunteers. Clinical trial registration number: ChiCTR-TRC-14004824.